IMPLEMENTASI METODE PEMBELAJARAN PENDIDIKAN KARAKTER ANAK USIA DINI DI PAUD PONDOK PESANTREN AL BAROKAH AJUNG JEMBER - Mahrus, Mahrus (LP2M IAIN Jember, 2020)
The problems will be examined in this study are: (1) How understanding the basic concept of the character of early childhood education in boarding school PAUD Al-Barokah, Ajung ? (2) How is implementation of learning methods of early childhood character education in PAUD Al Barokah Boarding School? (3) How to faced constraints in the process of implementation of character education in PAUD Al Barokah boarding school, Ajung.? This Research to know (1) Understanding the basic concept of the character of early childhood education in boarding school PAUD Al-Barokah, Ajung (2) Implementation of learning methods of early childhood character education in PAUD Al Barokah Boarding School (3) Faced constraints in the process of implementation of character education in PAUD Al Barokah boarding school, Ajung. This research was exploratory, qualitative method using the method of data collection by using the observation method, interview and documentation. And analyzed using the descriptive method, preparation of requirement and the validity of the data. Based in the presentation and analysis of data in general it can be concluded that (1) understanding of the basic concepts of early childhood character education in PAUD Al Barokah boarding school are quite diverse, (2) Implementation of learning methods of early childhood character education by using several methods, such as using Conditioning methods, Example, story, field trip and demonstration, (3) As for the barriers are is the language, the number of teachers, APE and textbooks. Permasalahan yang akan dikaji dalam penelitian ini adalah : (1)Bagaimana pemahaman konsep dasar pendidikan karakter anak usia dini di PAUD Pondok Pesantren Al Barokah Kecamatan Ajung, (2) Bagaimana inplementasi metode pembelajaran pendidikan karakter anak usia dini di PAUD Pondok Pesantren Al Barokah Kecamatan Ajung, (3) Bagaimana kendala-kendala yang dihadapi dalam menginplementasi metode pembelajaran pendidikan karakter di PAUD Pondok Pesantren Al Barokah Kecamatan Ajung. Adapun penelitian ini menggunakan metode kualitatif eksploratif, metode pengumpulan data dengan menggunakan metode abservasi, interview, dan dokumentasi. Dan dianalisis dengan menggunakan metode diskriptif, penyususnan katagori dan validitas data. Berdasarkan penyajian dan analisis data secara umum dapat disimpulkan bahwa (1) Pemahaman Konsep Dasar Pendidikan Karakter Anak Usia Dini di PAUD Pondok Pesantren Al Barokah Kecamatan Ajung cukup beragam,(2) Implementasi Metode Pembelajaran Pendidikan Karakter Anak Usia Dini dengan menggunakan beberapa metode, diantaranya adalah dengan menggunakan Metode Pembiasaan, Keteladanan, Kisah, Karyawisata dan demontrasi, (3) Adapun kendalanya adalah bahasa, jumlah tenaga pengajar, APE dan buku pelajaran.